Xanthotoxin (8‐methoxypsoralen): A review of its chemistry, pharmacology, pharmacokinetics, and toxicity. (1st August 2022) - Wu, Anxin; Lu, Jing; Zhong, Guofeng; Lu, Ling; Qu, Yan; Zhang, Chen
Abstract: Xanthotoxin (XAT) is a natural furanocoumarins, a bioactive psoralen isolated from the fruit of the Rutaceae plant Pepper, which has received increasing attention in recent years due to its wide source and low cost. By collecting and compiling literature on XAT, the results show that XAT exhibits significant activity in the treatment of various diseases, including neuroprotection, skin repair, osteoprotection, organ protection, anticancer, antiinflammatory, antioxidative stress and antibacterial. In this paper, we review the pharmacological activity and potential molecular mechanisms of XAT for the treatment of related diseases. The data suggest that XAT can mechanistically induce ROS production and promote apoptosis through mitochondrial or endoplasmic reticulum pathways, regulate NF‐κB, MAPK, JAK/STAT, Nrf2/HO‐1, MAPK, AKT/mTOR, and ERK1/2 signaling pathways to exert pharmacological effects. In addition, the pharmacokinetics properties and toxicity of XAT are discussed in this paper, further elucidating the relationship between structure and efficacy. It is worth noting that data from clinical studies of XAT are still scarce, limiting the use of XAT in the clinic, and in the future, more in‐depth studies are needed to determine the clinical efficacy of XAT.